The Diffusion of Detriment: Tracking Displacement Using a City-Wide Mixed Methods Approach - Hodgkinson, Tarah (The British journal of criminology, 2020)
Crime reduction strategies are often faced with the criticism of crime displacement. Conversely, criminologists find that reductions in crime in one area have a ‘diffusion of benefits' to surrounding areas. However, these findings are limited due to a lack of extensive longitudinal data and qualitative data that provide context. We examine a natural experiment in displacement: the removal of a convergence setting in which calls for service immediately declined. However, other areas emerged as problematic and, in some places, crime increased dramatically. Using a qualitatively informed trajectory analysis, we examine whether the removal of a convergence setting results in displacement across the entire city. We discuss the implications for opportunity theories and prevention strategies.